2019
DOI: 10.1029/2019gl085278
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale and Submesoscale Contributions to High Sea Surface Chlorophyll in Subtropical Gyres

Abstract: Mesoscale eddies in the oceans are known to modify the nutrient supply, stimulate phytoplankton growth, and significantly affect carbon fixation. Submesoscale processes associated with mesoscale eddies have been suggested to induce even stronger variability in phytoplankton dynamics; however, their large‐scale impact has not been quantitatively evaluated in the global ocean. By combining multiple satellite products to resolve both mesoscale and submesoscale dynamic regimes, we evaluated their contributions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…In addition to the mesoscale doming of the nutrients in the cyclonic meander of the LM, submesoscale vertical motions can drive the localized injection of nutrients into the euphotic layer. The vertical motion associated with submesoscale dynamics is much stronger than that associated with mesoscale dynamics (Mahadevan and Tandon, 2006;Capet et al, 2008a,b;Lévy et al, 2012;McWilliams, 2016;Brannigan et al, 2017;Guo et al, 2019) and could induce changes in phytoplankton growth or biomass (Martin and Richards, 2001;Klein and Lapeyre, 2009). As the small trigger meander is also a cyclonic eddy with the scale in the range of submesoscale, the nutrient could be supplied also through these submesoscale processes to the euphotic zone.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the mesoscale doming of the nutrients in the cyclonic meander of the LM, submesoscale vertical motions can drive the localized injection of nutrients into the euphotic layer. The vertical motion associated with submesoscale dynamics is much stronger than that associated with mesoscale dynamics (Mahadevan and Tandon, 2006;Capet et al, 2008a,b;Lévy et al, 2012;McWilliams, 2016;Brannigan et al, 2017;Guo et al, 2019) and could induce changes in phytoplankton growth or biomass (Martin and Richards, 2001;Klein and Lapeyre, 2009). As the small trigger meander is also a cyclonic eddy with the scale in the range of submesoscale, the nutrient could be supplied also through these submesoscale processes to the euphotic zone.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical studies often focus on phytoplankton, as the applicability of methods like remote sensing allows an investigation of the influence of smallscale structures in much easier and feasible ways compared to zooplankton research. With the aid of satellite data those studies identified increased chlorophyll concentrations associated with submesoscale fronts (Shulman et al, 2015;Liu and Levine, 2016;Guo et al, 2019).…”
Section: Accumulation Of Zooplankton Biomassmentioning
confidence: 99%
“…Due to their small spatial (0.1-10 km) and short temporal (hours to weeks) scales, in situ measurements, especially the assessment of their impact on biological processes, are difficult. Recent studies utilizing satellite data to analyze the effect of submesoscale fronts on phytoplankton revealed increased chlorophyll concentrations in such regions (Shulman et al, 2015;Liu and Levine, 2016;Guo et al, 2019). The main underlying cause is presumably due to the intense vertical velocities associated with small-scale dynamics, which lead to an enhanced upward transport of nutrients (Mahadevan and Archer, 2000;Mahadevan, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the lee of the Hawaiian Islands have identified several wind‐driven eddies that can increase phytoplankton production by injecting nutrients vertically (e.g., Benitez‐Nelson et al, 2007; Bidigare et al, 2003; Dickey et al, 2008; Seki et al, 2001). Submesoscale dynamics associated with mesoscale eddies have also been suggested to be able to induce chlorophyll anomalies and carbon export (e.g., Calil & Richards, 2010; Guidi et al, 2012; Guo et al, 2019; Lehahn et al, 2017; Liu & Levine, 2016).…”
Section: Introductionmentioning
confidence: 99%